2022
DOI: 10.1051/e3sconf/202234800029
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic effect ofBawang Dayakextracts (Eleutherine palmifolia(L.) Merr.) on Sprague Dawley rats

Abstract: The Dayak tribe in Kalimantan has long used bawang dayak as a traditional cure for various degenerative diseases. Previous research showed that bawang dayak bulb has an active compound that can inhibit the enzyme alpha-glucosidase, known as alpha-glucosidase inhibitor (AGI). Compounds that have such ability has a potential in controlling blood glucose level in diabetes mellitus. This research aims to study the effective dosage of aqueous extract and ethanolic extract of bawang dayak bulb as an AGI through an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
0
0
1
Order By: Relevance
“…The test results showed that the antioxidant activity of tilapia nuggets with Dayak onion ethanol extract coating was more significant than tilapia nuggets with Dayak onion water extract coating. In line with Febrinda et al (2022), the effective dose of Dayak onion water extract is greater than ethanolic extract in inhibiting the action of alpha-glucosidase enzymes. It shows that ethanol extract has a higher ability than aqueous extract to inhibit the activity of alpha glucosidase enzyme.…”
Section: Antioxidant Activitymentioning
confidence: 58%
“…The test results showed that the antioxidant activity of tilapia nuggets with Dayak onion ethanol extract coating was more significant than tilapia nuggets with Dayak onion water extract coating. In line with Febrinda et al (2022), the effective dose of Dayak onion water extract is greater than ethanolic extract in inhibiting the action of alpha-glucosidase enzymes. It shows that ethanol extract has a higher ability than aqueous extract to inhibit the activity of alpha glucosidase enzyme.…”
Section: Antioxidant Activitymentioning
confidence: 58%
“…glukosidase(Febrinda et al 2022), aktivitas antibakteri(Wicaksono et al, 2018), serta berpotensi sebagai antimikoba terhadap MRSA (methicilin-resistant Staphylococcus aureus) (Subramaniam et al 2012). dan hasil positif terbentuk warna merah coklat atau kuning.…”
unclassified